2020
DOI: 10.1007/s10902-020-00218-8
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude Texting Touches the Heart: Challenge/Threat Cardiovascular Responses to Gratitude Expression Predict Self-initiation of Gratitude Interventions in Daily Life

Abstract: Gratitude-based interventions are effective in facilitating positive relationships and increasing life satisfaction. However, for some individuals (e.g., with high levels of depression and low trait-gratitude) gratitude expression is threatening and rarely undertaken spontaneously. In this study, we expected to replicate this gratitude expression threat effect. Moreover, we aimed to understand psychophysiological mechanisms of this effect by accounting for cognitive, motivational, and physiological responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
0
9
0
1
Order By: Relevance
“…This suggests that self-reports are insufficient to explain physiology and, above all, behavior in the capitalization process. For instance, a recent study indicated the benefits of accounting for cardiovascular responses in positive psychological interventions because the cardiovascular response indicates the threat was predictive of lower behavioral engagement in the intervention (Enko et al 2020).…”
Section: A Multivariate Approach To Capitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that self-reports are insufficient to explain physiology and, above all, behavior in the capitalization process. For instance, a recent study indicated the benefits of accounting for cardiovascular responses in positive psychological interventions because the cardiovascular response indicates the threat was predictive of lower behavioral engagement in the intervention (Enko et al 2020).…”
Section: A Multivariate Approach To Capitalizationmentioning
confidence: 99%
“…Going beyond self-report is necessary for explaining which systems need to be engaged in individuals to achieve greater readiness for enthusiastic responding. Moreover, using physiological methods allows researchers to observe behavior without the interpretative difficulties inherent with self-reports (Enko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research in positive psychology has recently started to look at physiological measures. For instance, research has started to look at the link between positive psychology variables such as gratitude ( Enko et al, 2021 ) and emotions ( Kaczmarek et al, 2021 ) and cardiovascular responses. Such efforts in positive psychology are important.…”
Section: Introductionmentioning
confidence: 99%
“…The data for this study were derived from seven laboratory experiments that examined the psychophysiology of emotions [ 46 – 50 ]. Details about the studies are presented in ( S1 Table ).…”
Section: Methodsmentioning
confidence: 99%